A single-session positive cognitive intervention on first-year students' mental health: Short-term effectiveness and the mediating role of strengths knowledge. Issue 6 (18th August 2019) - Bu, He; Duan, Wenjie
Abstract: Objective: To better understand the effectiveness of a single-session positive cognitive intervention and uncover the possible mechanisms.Participants: Participants were 79 first-year students (aged 17–21) who volunteered for the intervention during the 2016 fall semester.Methods: Participants were randomly assigned into the intervention group and the control group. All participants completed pretest, post-test, 1 week, and 3-month follow-up tests. Thriving, negative emotional states, strengths knowledge were assessed.Results: Results showed significant increases of thriving in the intervention group at post-test and after 1 week, and significant decreases of negative emotions at the post-test and after 1 week and 3 months. Strengths knowledge fully mediated the intervention effect on thriving at post-test.Conclusions: The single-session positive cognitive intervention could be a responsive and effective approach to promote first-year students mental health. More attention should be paid to mechanisms of the single-session positive cognitive intervention so as to optimize the effects of the single-session positive cognitive intervention.